What constrains simultaneous mastery of first and second language word use?. (December 2016) - Malt, Barbara C.; Jobe, Rachel L.; Li, Ping; Pavlenko, Aneta; Ameel, Eef
Aims and objectives: We examined the bi-directional interaction of first language (L1) and second language (L2) word use patterns by asking whether L2 patterns of word use can be acquired with intensive exposure in a laboratory setting, and whether this early stage of L2 learning would impact L1 performance. Methodology: In two experiments, native speakers of English first labeled drinking vessels in English, then received intensive training on L2 Russian naming patterns for the objects, and, lastly, labeled the objects in English again. Data and analysis: Data were collected from eight different training groups with 14–15 participants each plus a control group with 14 participants who did not learn L2 Russian. Findings/conclusions: Trained participants successfully acquired L2 Russian patterns of word use regardless of specific training condition. However, they showed significantly less consistency in L1 English post-test labeling than the control group. Originality: Neither full acquisition of L2 patterns nor their simultaneous impact on L1 choices has been previously demonstrated. Significance/implications: These outcomes suggest that acquisition of target-like L2 word use can be facilitated by intensive exposure to word-referent mappings. However, even in the early stages of L2 learning, a L2 influence may be manifested in the L1 as a destabilization of word-to-referent mappings, suggesting continuous dynamic interaction between the two languages.